2021 IEEE PES Innovative Smart Grid Technologies Europe (ISGT Europe) 2021
DOI: 10.1109/isgteurope52324.2021.9640106
|View full text |Cite
|
Sign up to set email alerts
|

Power Oscillation Damping Using Converter- Interfaced Generators under Constrained Active and Reactive Powers

Abstract: Low-frequency oscillations are an inherent phenomena in transmission networks and renewable energy plants should be configured to damp them. Commonly, a centralised controller is used in PV plants to coordinate PV generators via communication channels. However, the communication systems of PV plants introduce delays of a stochastic nature that degrade the performance of centralised control algorithms. Therefore, controllers for oscillation damping may not operate correctly unless the communication channel char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…It has already been shown that this design method provides a system damping that is close to the optimal value [29]. Also, as the design is based on open-loop characteristics, the calculation of the compensator parameters can be easily automatised.…”
Section: Design Objectivementioning
confidence: 89%
See 3 more Smart Citations
“…It has already been shown that this design method provides a system damping that is close to the optimal value [29]. Also, as the design is based on open-loop characteristics, the calculation of the compensator parameters can be easily automatised.…”
Section: Design Objectivementioning
confidence: 89%
“…2, respectively. In [29], it has been shown that the criteria from (10) can be met by setting phases to zero for two open-loop functions separately:…”
Section: Design Objectivementioning
confidence: 99%
See 2 more Smart Citations
“…The POD controller will be designed by using the open-loop phase compensation method [27]. A simplified version of this method was previously presented in [28]. It was shown that the controller of each power loop should be designed separately and compensate the open-loop phase at the oscillation frequency of the corresponding plant.…”
Section: Pod Controller Designmentioning
confidence: 99%